Faktor-Faktor yang Mempengaruhi Pertumbuhan di 60 Kabupaten/Kota Sumbagsel Tahun 2017-2021 - Muhari, Muhammad Dheo Adrian; Machfudz, Masyhuri; Suprayitno, Eko (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Southern Sumatra, which consists of the provinces of South Sumatra, Lampung, Jambi, Bengkul, and the Bangka-Beelitung Islands province, has the fastest recovering economic growth compared to other provinces in Indonesia as well as being the highest recovery of economic growth in Sumatra from 2020-2021. By Therefore, this study aims to analyze what factors influence economic growth in 60 cities/regencies in SUMBAGSEL. Keywords: Factors, Economic Growth, SUMBAGSEL